Interleukin 2 Promotes Hepatic Regulatory T Cell Responses and Protects From Biliary Fibrosis in Murine Sclerosing Cholangitis. Issue 5 (30th September 2018) - Taylor, Amy E.; Carey, Alexandra N.; Kudira, Ramesh; Lages, Celine S.; Shi, Tiffany; Lam, Simon; Karns, Rebekah; Simmons, Julia; Shanmukhappa, Kumar; Almanan, Maha; Chougnet, Claire A.; Miethke, Alexander G.
Abstract : In the multidrug resistance protein 2 (Mdr2) ‐/‐ mouse model, low phospholipid bile instigates biliary epithelial injury, sterile inflammation, and fibrosis, thereby recapitulating disease mechanisms implicated in biliary atresia (BA) and primary sclerosing cholangitis. We hypothesize that T lymphocytes contribute to the biliary injury and fibrosis in murine sclerosing cholangitis (SC) and that they are susceptible to suppression by regulatory T cells (Tregs). In juvenile Mdr2 ‐/‐ mice, intrahepatic CD8+ lymphocytes were expanded, and contraction of intrahepatic Tregs coincided with rising serum alanine transferase and alkaline phosphatase (ALP) levels between days 14‐30 of life. Antibody‐mediated depletion of intrahepatic CD8+ lymphocytes during that time reduced ALP levels and the expression of osteopontin (Opn), a pro‐fibrogenic cytokine. Depletion of intrahepatic Tregs with anti‐CD25 antibody between days 7‐30 increased intrahepatic CD8+ T cells, Opn expression, and fibrosis. Conversely, expansion of intrahepatic Tregs with interleukin 2/anti‐interleukin 2 immune complexes (IL‐2c) downregulated hepatic expression of Opn and Tnf, reduced frequency of intrahepatic CD8+ lymphocytes, and diminished biliary injury and fibrosis. Treatment with IL‐2c upregulated hepatic Treg expression of CD39, an ectonucleotidase capable of hydrolyzing pro‐inflammatory adenosine triphosphate. In vitro, Tregs expressing CD39 suppressed the proliferation of hepatic CD8+ lymphocytes from Mdr2 ‐/‐ mice more efficiently than those lacking CD39. In infants with BA, infiltration of interlobular bile ducts with CD8+ cells was associated with biliary expression of Opn and its transcription was negatively correlated with mRNA expression of Treg‐associated genes. Conclusion: Hepatic CD8+ T lymphocytes drive biliary injury and fibrosis in murine SC. Their proliferation is controlled by hepatic Tregs through the purinergic pathway, which is responsive to IL‐2c, suggesting that Treg‐directed low‐dose Il‐2 treatment may be considered as therapy for SC.